Cognitive assessment of risk-taking behavior in adults with substance use disorders and internet addiction. - Chhag, Hrutul; Leon, Chaithanya; Kaur, Simran; Balhara, Yatan Pal Singh; Kaur, Ravneet; Sharma, Ratna (Indian Journal of Psychiatry, 2026)
Background: Individuals with substance use and internet addiction disorders have a greater likelihood to indulge in risky behavior and show signs of impairment in self-regulation. Risk-taking behavior depends on reward seeking, impulsiveness, and cognitive control systems such as executive functioning, cognitive flexibility, and working memory. Assessment using cognitive tasks and validated questionnaires can provide an insight into the risk-taking behavior of these individuals. Aim: To assess the risk-taking behavior in adults with substance use disorders (SUDs) and internet addiction, by both subjective and objective assessment methods compared to matched healthy controls. Methods: This cross-sectional observational study included 120 participants comprising 60 adults with SUDs (30 subjects each with opioid use disorder, alcohol use disorder (AUD)), 30 with internet addiction (IA), and 30 matched healthy volunteers. Each participant performed an objective cognitive function task (Balloon Analogue Risk Task (BART)) and subjective questionnaires were administered (risk-taking questionnaire, brief self-control scale, and Eysenck impulsivity subscale). Results: Subjects with opioid use disorder were found to have poor self-control (37 ± 9.052 vs 44.4 ± 7.686, P < 0.01) and higher risk-taking score (12.13 ± 2.32 vs 9 ± 1.576, P < 0.0001) as compared to controls. Further, they also exhibited higher median reaction time (all pumps, safe bets) during BART compared to controls (18.57 (12.49–24.34) vs 9.81 (6.23–11.34), P < 0.0001 and 21.64 (13.66–36.59) vs 10.64 (6.8–12.59), P < 0. 0001, respectively), AUD (18.57 (12.49–24.34) vs 10.75 (8.84–17.65), P < 0.05 and 21.64 (13.66–36.59) vs 11.83 (9.28–21.52), P < 0.05, respectively), and IA groups (18.57 (12.49–24.34) vs 9.92 (7.92–11.90), P < 0.0001 and 21.64 (13.66–36.59) vs 11.34 (8.95–13.71), P < 0.001, respectively). Conclusion: Among all participants with SUDs and IA, those with opioid use disorder exhibited higher risk taking, as assessed by subjective and objective measures.